Fluctuations of Imbalanced Fermionic Superfluids in Two Dimensions Induce Continuous Quantum Phase Transitions and Non-Fermi-Liquid Behavior - Philipp Strack (Physical Review X, 2014)
We study the nature of superfluid pairing in imbalanced Fermi mixtures in two spatial dimensions. We present evidence that the combined effect of Fermi surface mismatch and order parameter fluctuations of the superfluid condensate can lead to continuous quantum phase transitions from a normal Fermi mixture to an intermediate Sarma-Liu-Wilczek superfluid with two gapless Fermi surfaces—even when mean-field theory (incorrectly) predicts a first-order transition to a phase-separated “Bardeen-Cooper-Schrieffer plus excess fermions” ground state. We propose a mechanism for non-Fermi-liquid behavior from repeated scattering processes between the two Fermi surfaces and fluctuating Cooper pairs. Prospects for experimental observation with ultracold atoms are discussed.